Using Output-based Aid in Urban Projects - Ahmed, Wajiha; Menzies, Iain (World Bank, Washington, DC, 2013)
Against the backdrop of rapidly rising urbanization in the developing world and the growing demand for basic services such as water and power, there is an increasing need to improve service delivery, particularly in low-income urban settlements. Output-based aid (OBA) approaches, with their pro-poor targeting, have been piloted in cities around the world. This note discusses the benefits and challenges of using an OBA approach in urban projects for low-income residents, provides examples of successful innovations, and highlights features that will improve the likelihood of success.